Use of smartphone applications to improve quality of bowel preparation for colonoscopy: a systematic review and meta-analysis - Desai, Madhav; Nutalapati, Venkat; Bansal, Ajay; Buckles, Daniel; Bonino, John; Olyaee, Mojtaba; Rastogi, Amit (Endoscopy International Open, 2019)
Introduction Smartphone-based applications (apps) have been used to improve the quality of bowel preparation (prep) but the success rates have been variable. We have performed a systematic review and meta-analysis to evaluate the impact of smartphone apps on bowel preparation.Methods Electronic databases (MEDLINE, Embase, CINAHL and Cochrane) were reviewed for eligible studies of smartphone apps versus standard education before colonoscopy. The following outcomes were analyzed: pooled rate of adequacy of bowel prep among both arms and Boston bowel preparation score (BBPS) when reported. Pooled analysis was reported as odds ratio (OR) or mean difference in random effect model with Review Manager 5.3 (P ≤ 0.05 for statistical significance). Results Six studies were eligible with smartphone app (810 patients) vs. standard education (855 patients, control group) for bowel prep. The smartphone app group had a higher proportion of adequate bowel prep compared to the control group: 87.5 % vs 77.5 % (five studies), pooled OR 2.67; 95 %CI 1.00 – 7.13 with P = 0.05. There was substantial heterogeneity in studies with I2 = 78 %. When analysis was limited to randomized controlled trials (RCTs), smartphone app users had a numerically higher rate of bowel cleansing: 87.1 % vs 76.9 %; however, pooled OR was not statistically significant (OR 2.66, 95 %CI 0.92 – 7.69, P = 0.07). When studies using BBPS were evaluated (n = 3), smartphone app users had higher mean scores (better bowel prep) with a mean difference of 0.9 (95 %CI 0.5 – 1.3), which was statistically significant (P < 0.01).Conclusion The smartphone app is a novel educational tool that can assist in achieving adequate and better bowel cleansing before colonoscopy.